THE FINDING OF THEME AND RHEME TYPE IN THE JAKARTA POST ARTICLE - Kristanto Cecario; Ida Lisdawati (IKIP Siliwangi, 2022)
In finding out the meaning of language, people should know how to understand the language whether by context or text. In Functional Linguistic, one of ways to find the text meaning can use the theme and rheme analysis. The theme and rheme analysis focus on the massage of clause in the text. Theme is the main idea from the clause and rheme is the rest of clause that explain the main theme. Based on Gerot and Wignell, 1994 cited in (Puspa, 2016) Theme is, broadly speaking, what the clause is going to be about. The rest of the clause is called the Rheme. In other word, theme represents the idea represented by the constituent at the starting point of the clause and Rheme represents the rest of message.The researchers decided to analysis the use of theme and rheme in The Jakarta Post article to find out the type of theme and rheme analysis connecting one clause to another. The methodology that uses in this research is qualitative descriptive and data collected with analysis the text. The conclusion of this research is that most of the themes used in this text are topical themes Keywords: Clause, Functional Linguistics, Theme and Rheme